2022
DOI: 10.3389/fpubh.2022.769898
|View full text |Cite
|
Sign up to set email alerts
|

Rabies Elimination in Rural Kenya: Need for Improved Availability of Human Vaccines, Awareness and Knowledge on Rabies and Its Management Among Healthcare Workers

Abstract: BackgroundIn Africa, rabies causes an estimated 24,000 human deaths annually. Mass dog vaccinations coupled with timely post-exposure prophylaxis (PEP) for dog-bite patients are the main interventions to eliminate human rabies deaths. A well-informed healthcare workforce and the availability and accessibility of rabies biologicals at health facilities are critical in reducing rabies deaths. We assessed awareness and knowledge regarding rabies and the management of rabies among healthcare workers, and PEP avail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…A previous study showed most dogs in rural areas roamed freely and were not required registration, posing a significant risk of infection and transmission of rabies [ 5 ]. In addition, people in rural areas had weak awareness of rabies prevention [ 40 – 42 ].Previous studies showed rural areas in China were still the main source of rabies transmission, and improving the awareness of rabies prevention in rural areas is still one of the main measures to eliminate human rabies [ 8 , 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed most dogs in rural areas roamed freely and were not required registration, posing a significant risk of infection and transmission of rabies [ 5 ]. In addition, people in rural areas had weak awareness of rabies prevention [ 40 – 42 ].Previous studies showed rural areas in China were still the main source of rabies transmission, and improving the awareness of rabies prevention in rural areas is still one of the main measures to eliminate human rabies [ 8 , 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…6,7 Rabies is considered to be endemic in Kenya, with an estimated 523 human deaths (95% confidence interval [CI] 134-1100) annually; hence, dog bites are an important public health risk. 8 Although there is a dearth of information on the global estimates of dog-bite incidence, studies suggest that tens of millions suffer from dog-bite injuries, causing deaths in an estimated 59,000 individuals annually. 9 In the United States, approximately 4.5 million dog bites take place annually, while an estimated 1870 bites per 100,000 population occur annually in the UK.…”
Section: Introductionmentioning
confidence: 99%
“…Dogs are responsible for the transmission of zoonoses, particularly rabies virus, where they account for more than 99% of human rabies cases and approximately 22,000 people die annually of rabies in Africa alone 6,7 . Rabies is considered to be endemic in Kenya, with an estimated 523 human deaths (95% confidence interval [CI] 134–1100) annually; hence, dog bites are an important public health risk 8 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kenya has a >100-year history of rabies; the first case was reported in 1912 ( 23 ). Despite successful control efforts in the past, the disease has remained endemic because of challenges in sustaining vaccination programs ( 24 , 25 ). The number of human deaths attributable to rabies in Kenya is unknown ( 23 ), but some studies report estimates of >2,000 per year and others as low as 523 ( 26 , 27 ); the highest incidences have been reported in western and eastern Kenya ( 23 ).…”
mentioning
confidence: 99%